(untitled) (Indian Internet Journal of Forensic Medicine and Toxicology, 2013)
The purpose of this research was to determine the impact of age and microbial growth on the benzidine and phenolphthalein tests along with blood grouping. The paper compared the efficacy of the absorption elution method to that of the ammonia extraction method for blood grouping. In this study, 50 bloodstained samples spanning a decade in age were tested. The accuracy of the benzidine test was 90% and that of the phenolphthalein test was 86%. It was found that age played no role in both preliminary tests nor in blood grouping. Ammonia extraction proved to be more effective than absorption elution with an accuracy of 69% versus 61%. Owing to the absence of impact of age on the samples, microbial growth was studied in detail. On in-vitro culturing, samples showed the presence of various cultures including bacteria, fungi such as Aspergillus and Penicillium and an abundance of yeasts. Based on the experimental findings, it is evident that even on samples with no visible contamination, extensive microbial colonisation can occur. Such growth can also effect the efficiency of performed tests producing false positives and negatives. This highlights the issue of necessary reformations to current practices to improve quality of investigations.